Formation of a complex between TMEM217 and the sodium-proton exchanger SLC9C1 is crucial for mouse sperm motility and male fertility - Rie Iida-Norita; Haruhiko Miyata; Akinori Ninomiya; Chihiro Emori; Maki Kamoshita; Chen Pan; Haoting Wang; Masahito Ikawa (Proceedings of the National Academy of Sciences, 2025)
Sperm motility is essential for male fertility and is tightly controlled by signaling events in the flagellum. Slc9c1 encodes a sperm-specific Na + /H + exchanger (sNHE/SLC9C1) that localizes to the flagellum and is indispensable for sperm motility and male fertility. SLC9C1 is unique among Na + /H + exchangers in that it possesses a voltage-sensing domain (VSD), the physiological function of which remains poorly understood in mammals. Here, by analyzing coevolving genes with Slc9c1 , we identified Tmem217 , which encodes a transmembrane protein that is localized in the sperm flagellum. Knockout (KO) of Tmem217 in mice resulted in sperm motility defects and male infertility, phenocopying Slc9c1 KO mice. Coimmunoprecipitation and structural prediction analyses indicated that TMEM217 binds to SLC9C1 via its VSD. Further analyses indicated that the amounts of SLC9C1 and its associated protein, soluble adenylyl cyclase (sAC), were lost in mature Tmem217 KO spermatozoa, leading to disrupted 3′,5′-cyclic monophosphate (cAMP) signaling pathways. Remarkably, cAMP analogs restored the impaired motility and fertilizing ability of Tmem217 KO spermatozoa in vitro, validating the essential role of TMEM217 in regulating cAMP production. Our findings indicate that the association of TMEM217 with SLC9C1 via its VSD is critical for the proper organization and function of the SLC9C1–sAC–cAMP axis in mature spermatozoa.